2020
DOI: 10.1209/0295-5075/132/44001
|View full text |Cite
|
Sign up to set email alerts
|

Buckling and snapping of a thin polymeric membrane exposed to a solvent drop

Abstract: We report the behavior of a thin and flat rectangular polymeric membrane, fixed at both ends, in contact with a solvent droplet. Depending on the solvent type and volume, and membrane thickness, three different regimes —no buckling, buckling, and snapping— are observed. Our study reveals that the behavior depends on the solubility parameter of the solvent and the ratio of the sum of swelling-induced force and capillary force to the elastic restoring force, i.e., the force ratio. We attempt to explain the pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The third mechanism is related to the existence of gradients of the moisture content or liquid content in the thickness direction of the paper sheet. Holmes et al , 17 Samy et al 56 and Sun et al 57 reported on experiments regarding the deposition of solvent droplets on polymer sheets. The solvent swells the top part of the polymer which induces a curvature corresponding to an upwards displacement.…”
Section: Discussionmentioning
confidence: 99%
“…The third mechanism is related to the existence of gradients of the moisture content or liquid content in the thickness direction of the paper sheet. Holmes et al , 17 Samy et al 56 and Sun et al 57 reported on experiments regarding the deposition of solvent droplets on polymer sheets. The solvent swells the top part of the polymer which induces a curvature corresponding to an upwards displacement.…”
Section: Discussionmentioning
confidence: 99%
“…2d and e respectively), which are consistent with values reported in the literature. 61,62 The obtained PDMS surface is considered rigid since the elastocapillary number length 63,64 (g/E) , where g is the liquid surface tension and E is the Young's modulus of PDMS, 65 is considered to be low (z10 À8 m). To achieve hydrophobic surface, the spin-coated PDMS layer is cured at 180 C for 90 min, 66 and the WCA is measured to be 110 AE 0.3 (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…stiction, breakage, and collapse) driven by capillary forces. For instance, the deposition of a volatile liquid solvent droplet on a polydimethylsiloxane (PDMS) membrane with a thickness of approximately 100 µm leads to membrane buckling due to swelling effects [31]. Furthermore, swellinginduced membrane deformation facilitates self-driven droplet motion and spontaneous oscillations [32].…”
Section: Introductionmentioning
confidence: 99%